Effects of dexmedetomidine infusion during spinal anesthesia on hemodynamics and sedation. Issue 1 (1st January 2018) - Tarıkçı Kılıç, Ebru; Aydın, Gaye
ABSTRACT: Background : We evaluated the effects of intravenous dexmedetomidine during spinal anesthesia on hemodynamics, respiratory rate, oxygen saturation, sedpain, and compared them with those of saline infusion. Sixty American Society of Anesthesiologists physical status I and II cases were randomly divided into two groups. Patients were connected to the monitor after premedication, and spinal anesthesia was administered. Sensory and motor blockades were assessed using pinprick test and Bromage scale, respectively. Group I received dexmedetomidine infusion and Group II received saline infusion. Throughout the infusion process, hemodynamic data, respiratory rate, oxygen saturation, sedation, pain, Bromage score, amnesia, bispectral index, and side effects were recorded. Postoperative hemodynamic measurements, oxygen saturation, sedation, pain scores were obtained. Sedation and pain were evaluated using the Ramsay and visual analog scales, respectively. Analgesics were administered in cases with high scores on the visual analog scale. Postoperative analgesic consumption, side effects, treatments were recorded. No significant differences were found between the groups with respect to oxygen saturation, respiratory rate, pain, and side effects in the intraoperative period. Time to onset of sensorial block, maximum sensorial block, onset of motor block, and maximum motor block; bispectral index values; and apex heartbeat until 80 min of infusion, systolic arterial blood pressure until 90 min, and diastolic arterial blood pressure until 50 min were lower, whereas amnesia and sedation levels were higher in dexmedetomidine group. Postoperative pain and analgesic requirement were not different. Apex heartbeat at 15 min and systolic arterial blood pressure at 30 min were lower and sedation scores were higher in the dexmedetomidine infusion group. We demonstrated dexmedetomidine infusion had a hemodynamic depressant effect intraoperatively whereas it had no significant effect on peripheral oxygen saturation, respiratory rate, visual analog scale scores, and side effects. Dexmedetomidine infusion enhanced motor and sensory blockade quality and induced amnesia and sedation.